The Impact of International Standards (IAS/IFRS) on Financial Analysis: Case Study of ENIEM - Badi, Abd elmadjid; makhloufi, Tahar; Garadi, Abd kader (Finance and Business Economies Review, 2022)
This article deals with how to do the financial analysis according to the standards (IAS/IFRS), adopted by the Algerian Financial Accounting System (SCF-2007), which was applied to Algerian institutions on January 1, 2010. It was found from the applied study (the case of ENIEM Corporation) that the preparation of its financial statements according to the international accounting standards, this preparation greatly facilitated the study of the budget and calculating the result using the tools of financial analysis, where a judgment was reached on the financial position of the institution. The results show than we can make an easy financial analysis in the context of (SCF-2007), and (IAS/IFRS), the enterprise has a structural equilibrium in the long term, but it has some difficulties in the short term.